A thematic analysis of care provider experiences of using self‐harm abstinence agreements in psychiatric inpatient care - Jonas Bjärehed; Evelina Ingelsson Lindell; Sofie Westling (Nursing Open, 2021)
Abstract Aim Traditional methods used when managing self‐harm in a psychiatric inpatient setting tend to infringe on the autonomy of the individuals receiving treatment and are often experienced as practically and emotionally challenging by care providers. Therefore, we examined care providers’ experiences of an alternative method negotiating self‐harm abstinence agreements, which can be viewed as a form of positive risk taking. Design A qualitative approach using semi‐structured interviews with twelve mental health professionals. Methods Thematic analysis of the interviews. Results Five themes emerged; “No‐harm agreements versus constant observation and coercion,” “No‐harm agreements to promote independence and collaboration,” “No‐harm agreements’ effect on ward safety,” “Ambiguity surrounding the no‐harm agreements” and “Ethical complexities of the no‐harm agreements.” These indicated perceived positive effects on the therapeutic relationship, the individuals’ autonomous functioning and the ward environment, but also practical and ethical difficulties.